Method for improving fatigue strength of deformed Mg-Al magnesium alloy

Through the dual purification scheme of ‘raw material removal + process control’, Mg-Al-based magnesium alloy with strong base surface texture and uniform refinement was prepared, which solved the problem of low fatigue strength of existing magnesium alloys and achieved high fatigue strength and low cost preparation effects.

CN119876654APending Publication Date: 2025-04-25XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510052347.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing Mg-Al-type deformed magnesium alloy has low fatigue strength and is difficult to meet the safety and stability needs of lightweight commercial vehicles.

Method used

Using the dual purification scheme of ‘raw material removal + process control’, the Mg-Al-based magnesium alloy with strong base surface texture and uniform refinement was prepared through the purification and smelting ingot, homogenization treatment and extrusion forming process of high-purity raw materials.

Benefits of technology

It effectively improves the tensile strength and elongation of breaking of Mg-Al-based deformed magnesium alloy, reduces the inclusion content, inhibits the initiation of fatigue cracks, and realizes the preparation of high-quality magnesium alloys with high fatigue strength at low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876654A_ABST
    Figure CN119876654A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the fatigue strength of a deformed Mg-Al magnesium alloy. The method comprises the following steps: 1, preparing a high-purity magnesium alloy clean and dense cast ingot, designing the alloy according to Mg (2.5-3.5) Al (0.6-1.4) Zn (0.2-1.0) Mn (wt.%), and obtaining alloy raw materials; 2, a purified magnesium alloy semi-continuous casting system is adopted; 3, after the alloy raw materials are put into a semi-continuous casting system, the alloy raw materials are put into the semi-continuous casting system to be cast, a semi-continuous casting rod is obtained, and the semi-continuous casting rod is scalped to obtain an AZ31 alloy cast ingot; and 4, the AZ31 alloy ingot obtained in the step 3 is subjected to plastic forming, and the anti-fatigue Mg-Al magnesium alloy is obtained. According to the method, the high-quality Mg-Al wrought magnesium alloy with high fatigue strength is prepared at low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of Mg-Al series magnesium alloys, and in particular to a method for improving the fatigue strength of a deformed Mg-Al series magnesium alloy. Background Art

[0002] Magnesium alloy is one of the lightest metal structural materials (density 1.7-2.0g / cm 3 ), efficiently assembling deformed magnesium alloy profiles into large-load and highly reliable magnesium alloy commercial vehicle structural units is particularly critical to reducing the dead weight of new energy commercial vehicles and further improving freight efficiency. The structure of magnesium alloy commercial vehicles will inevitably withstand alternating or pulsating fatigue strains such as torsion, bending, tension and compression during service. At this time, fatigue strength is often one of the important design parameters of automotive magnesium alloy structural materials. According to statistics, fatigue fracture is the main form of failure of vehicle body structures. During fatigue fracture, the maximum bearing stress of the structure is generally lower than the tensile strength of the metal material, or even lower than the yield strength. Fatigue fracture is often a low-stress fracture without obvious plastic deformation. Therefore, improving the fatigue performance of magnesium alloy structural materials is urgent and necessary to ensure the safe and stable service of lightweight commercial vehicles.

[0003] Mg-Al magnesium alloys are the most mature commercially available deformable magnesium alloys. They are generally processed through plastic deformation to achieve uniform microstructure refinement and improved mechanical properties. They are expected to further optimize the lightweight design of large load-bearing structures of commercial vehicles (such as ton-class magnesium alloy trailer bodies).

[0004] At present, the uniaxial tensile fatigue strength (stress ratio R = 0.1) of common commercial deformed magnesium alloys (such as AZ31 magnesium alloy) is in the range of 72-97MPa, which is still a certain gap compared with the uniaxial tensile fatigue strength (stress ratio R = 0.1, 80-118MPa) of mainstream automotive aluminum alloy profiles (such as 6082). Therefore, it is necessary to further improve the fatigue strength of Mg-Al deformed magnesium alloy materials to ensure the safe service of magnesium alloy lightweight commercial vehicles.

[0005] At present, there are two main factors that affect the fatigue performance of materials: 1. Controlling factors that easily induce fatigue crack initiation, such as inclusions, inhibiting the generation of fatigue crack sources to improve fatigue strength and fatigue life; 2. Improving fatigue life by controlling the fatigue crack propagation rate.

[0006] In the prior art, the methods for improving the fatigue performance of deformed magnesium alloys mainly include reducing the grain size, surface treatment and adding rare earth metal elements.

[0007] Reducing the grain size mainly improves the fatigue properties of the material by controlling the growth rate of fatigue cracks. At present, the most common method for preparing ultrafine-grained magnesium alloy samples is equal channel angular pressing (ECAP). For example, in the literature [Tsushida M, Shikada K, Kitahara H, et al. Relationship between fatigue strength and grain size in AZ31 magnesium alloys [J]. Materials transactions, 2008, 49 (5): 1157-1161. Kim HK, Lee YI, Chung CS. Fatigue properties of a fine-grained magnesium alloy produced by equal channel angular pressing [J]. Scripta Materialia, 2005, 52 (6): 473-477.], a series of AZ31 magnesium alloys with different grain sizes were prepared by equal channel angular pressing, and the fatigue strength can be improved by refinement. Reducing the grain size can improve the ability of the material to hinder crack propagation and inhibit crack propagation; at the same time, cracks in larger grains tend to propagate more easily along grain boundaries or slip bands, which accelerates the fatigue fracture of the material. However, the disadvantage is that repeated extrusion not only leads to increased manufacturing costs, but also further grain refinement caused by excessive extrusion will produce anti-Hall-Petch-induced yield strength and crack nucleation resistance, resulting in a decrease in fatigue strength.

[0008] Surface treatment improves the fatigue performance of materials by inhibiting the initiation of fatigue cracks. Surface treatment methods can inhibit the initiation of fatigue cracks on the surface of materials. For example, in the literature [Fouad Y, Mhaede M, Wagner L. Effects of mechanical surface treatments on fatigue performance of extruded ZK60 alloy [J]. Fatigue & Fracture of Engineering Materials & Structures, 2011, 34 (6): 403-407.], the surface of magnesium alloy is strengthened by shot peening (SP) and ball grinding (BB) to improve its fatigue resistance. It suppresses the generation of surface fatigue crack sources and improves fatigue strength and fatigue life by applying a residual compressive stress layer and a fine grain layer near the surface of the material. However, its disadvantage is that improper parameters can cause surface damage to induce crack initiation. For example, excessively large polishing balls and shot peening ball diameters can cause microcracks on the surface of the material, which are surface damage that is conducive to the initiation of fatigue cracks.

[0009] The addition of rare earth elements mainly improves the fatigue performance of materials by controlling the propagation rate of fatigue cracks. Alloying can improve the tension-compression asymmetry of magnesium alloys by activating the basal slip system, thereby improving the fatigue resistance of magnesium alloys. For example, in the literature [Yang F, Lv F, Yang XM, et al. Enhanced very high cycle fatigue performance of extruded Mg–12Gd–3Y–0.5Zr magnesium alloy [J]. Materials Science and Engineering: A, 2011, 528 (6): 2231-2238.], by adding a total amount of rare earth elements (gadolinium, yttrium, zirconium, etc.) exceeding 15.5wt.%, the fatigue strength under uniaxial tension and compression (R = -1) conditions was improved. However, the disadvantage is that the addition of up to 15.5wt.% of rare earth alloying elements greatly increases the cost of raw materials, which is not conducive to widespread promotion.

[0010] However, the above methods of improving material fatigue strength often require high costs, and are accompanied by disadvantages such as complicated processes, low efficiency, and poor stability. Summary of the invention

[0011] In order to overcome the defects of the above existing technologies, the present invention provides a method for improving the fatigue strength of deformed Mg-Al magnesium alloys. The method adopts a dual purification scheme of "raw material impurity removal + process impurity control". Through high-purity raw materials-clean smelting ingots-homogenization treatment-extrusion forming process, a deformed Mg-Al alloy with strong basal texture and uniform and refined structure is obtained, which has high tensile strength and elongation at break; secondly, the dual purification scheme of "raw material impurity removal + process impurity control" effectively reduces the inclusion content in the magnesium alloy and inhibits the initiation of fatigue cracks. The above-mentioned strong basal texture-low-density inclusion distribution realizes the low-cost preparation of high-quality Mg-Al deformed magnesium alloys with high fatigue strength.

[0012] In order to achieve the above object, the technical solution adopted by the present invention is:

[0013] A method for improving the fatigue strength of a deformed Mg-Al magnesium alloy comprises the following steps:

[0014] Step 1: Select alloy raw materials Mg, Al, Zn and Mn, in which the Al content is 2.5-3.5%, the Zn content is 0.6-1.4%, the Mn content is 0.2-1.0, and the balance is Mg.

[0015] Step 2: placing the alloy raw material into a semi-continuous casting system, and then placing the alloy raw material into the semi-continuous casting system for casting to obtain a semi-continuous cast rod, and performing a peeling treatment on the semi-continuous cast rod to obtain an AZ31 alloy ingot;

[0016] Step 3: Plastically forming the AZ31 alloy ingot obtained in step 2 to obtain a fatigue-resistant Mg-Al magnesium alloy.

[0017] The step 1 is specifically as follows:

[0018] (a) Assembling graphite parts; placing raw magnesium to be purified into the graphite parts;

[0019] (b) The assembled graphite parts are placed into the corundum tube of the electric furnace and sealed with a flange;

[0020] (c) Turn on the vacuum pump switch, and when the vacuum degree in the corundum tube reaches below 10Pa, start the circuit heating;

[0021] (d) After heating is completed, wait for the electric furnace to cool naturally to below 50° C., close the vacuum valve and vacuum pump, then open the electric furnace flange valve to return the pressure in the corundum tube to normal pressure, finally punch the flange to take out the graphite part, and take out the purified high-purity crystalline magnesium;

[0022] (e) assembling a graphite piece, and loading high-purity crystalline magnesium into a raw material area in the graphite piece;

[0023] (f) Place the assembled graphite parts into the corundum tube of the electric furnace and seal it with a flange; turn on the vacuum pump switch and close the vacuum valve when the vacuum degree reaches below 50Pa;

[0024] (g) Open the argon valve and gas flow meter, and when the pressure in the tube returns to normal pressure, close the argon valve;

[0025] (h) Repeat (f) and (g) 2-3 times to complete the gas washing, then open the argon valve and the gas outlet at the other end of the furnace tube, adjust the flow rate of the flow meter to maintain the micro-flow state in the tube;

[0026] (i) The upper and middle temperature zones of the electric furnace are set to 900°C (raw material zone), and the lower temperature zone (ingot zone) is set to 830°C, with a heating rate of 10°C / min and a holding time of 600 min; (The upper and middle temperature zones are both raw material zones, so their temperature settings need to ensure that the high-purity crystalline magnesium in the raw material zone is smoothly vaporized and flows into the ingot zone below along the downward airflow direction. The temperature is set slightly lower than that of the raw material zone to ensure that the downward airflow direction ensures that the magnesium vapor can smoothly enter the ingot zone.)

[0027] (j) After the insulation is completed, the electric furnace needs to be cooled naturally to below 50°C, and then the argon valve can be closed, the flange can be opened and the graphite parts can be removed to obtain a high-purity magnesium alloy net dense ingot;

[0028] (k) Using laboratory-made high-purity magnesium (i.e., high-purity magnesium alloy net dense ingot) (99.98%), pure aluminum (99.85%), pure zinc (99.995%), and anhydrous manganese chloride (98.38%, water-insoluble matter ≤ 0.005); the alloy is designed according to the composition of Mg-(2.5-3.5)Al-(0.6-1.4)Zn-(0.2-1.0)Mn (wt.%).

[0029] In said (a):

[0030] Arrange the graphite parts in the order of a1-a13, with a1 using a 50mm long graphite part and a2-a13 using 100mm long graphite parts;

[0031] The graphite blind plate b1 is placed between the graphite piece a5 and the graphite piece a6, the seven-hole graphite plate b2 is placed between the graphite piece a8 and the graphite piece a9, and the graphite blind plate b3 is placed between the graphite piece a10 and the graphite piece a11;

[0032] The graphite parts are connected by internal and external threads, and are cylindrical hollow structures;

[0033] Put the raw magnesium to be purified into the a6 graphite part;

[0034] Graphite piece a6 is the evaporation zone, graphite piece a6 to graphite piece a9 are the gas phase channels, and graphite piece a10 is the condensation zone;

[0035] The evaporation zone is the lower temperature zone, the graphite parts a7 and a8 of the gas phase channel are located in the middle temperature zone, and the graphite part a9 and the condensation zone are located in the upper temperature zone.

[0036] In said (c):

[0037] The heating speed is controlled by setting the set temperature and heating time in the three-temperature zone control panel; taking the evaporation curve as an example (the time is the accumulated result, the actual working time needs to subtract the previous time, for example, the insulation time is 80min-50min=30min), first set the initial temperature of the evaporation end to 0 and the time to 0; set the temperature to 400° and the time to 50min; set the temperature to 400° and the time to 80min (insulation); set the temperature to 650° and the time to 105min; set the temperature to 750° and the time to 115min; set the temperature to 900° and the time to 130min; set the temperature to 900° and the time to 530min; set the temperature to 750° and the time to 560min; set the temperature to 650° and the time to 580min; set the temperature to 500° and the time to 610min; finally, set the end code according to the end code of the furnace of different models.

[0038] In (e), the graphite pieces are arranged in the order of a1-a13, and a13 uses a 50 mm long graphite piece, and a1-a12 use a 100 mm long graphite piece;

[0039] The graphite blind plate b1 is placed between the graphite piece a4 and the graphite piece a5, the seven-hole graphite plate b2 is placed between the graphite piece a6 and the graphite piece a5, and the graphite blind plate b3 is placed between the graphite piece a10 and the graphite piece a11;

[0040] The graphite parts are connected by internal and external threads, and are cylindrical hollow structures;

[0041] Graphite parts a5 and a6 are ingot areas, and graphite parts a7 to a10 are raw material areas.

[0042] The step 2 is specifically as follows:

[0043] The semi-continuous casting system includes a crucible, a liquid guide tube and a crystallizer connected in sequence. The crucible is a high-purity and high-density graphite crucible with a volume density of 1.82-1.85g / cm 3 , thermal conductivity 85W / (m·K), ash content 500ppm, purified ash content 11ppm, particle size 8-11μm; the liquid guide tube is made of 304 stainless steel; the crystallizer adopts graphite inner wall; the cooling medium is industrial water.

[0044] The step 3 is specifically as follows:

[0045] a) Stepwise heating protection standby: The debugged and purified magnesium alloy semi-continuous casting system is heated to 300℃±50℃ for insulation, and the exposed area of ​​the graphite crucible is heated to 600℃±50℃ for insulation with argon protection, and then heated to 835℃±50℃ for standby use. The subsequent processes are all carried out under a mixed protective atmosphere of high-purity argon + high-purity CO2 + sulfur hexafluoride, where the flow rate ratio of CO2 to SF6 is 100:1;

[0046] b) Main alloy melt testing: According to Mg-(2.5-3.5)Al-(0.6-1.4)Zn-(0.2-1.0)Mn (wt.%), the alloy ratio composition and alloy element burnout rate are carried out. First, high-purity magnesium is put into the crucible and fully melted. The temperature is set to 855℃±50℃. Then, pure zinc and pure aluminum ingots are put into the crucible, fully stirred and anhydrous MnCl2 is added;

[0047] After all the input materials are melted, stir them in the solution for about 10-15 minutes with argon protection; use No. 5 flux with a mass ratio of about 1-3% of the total melt mass to refine at 740-750℃ for 10-15 minutes, stir them in the solution with argon, and take the melt sample for the first pre-furnace composition test;

[0048] c) alloy composition adjustment: add pure magnesium, pure zinc, pure aluminum, anhydrous MnCl2, adjust the alloy composition, and then conduct secondary refining, use No. 5 flux with a mass ratio of about 1-3% of the total melt mass at 740-750°C, and stir the solution with argon for about 10-15 minutes; take a sample of the melt for a second furnace pre-composition test to ensure that the micro-element alloy composition is within the set range ((0.2-1.0)Mn (wt.%));

[0049] The composition is based on the above design composition: Mg-(2.5-3.5)Al-(0.6-1.4)Zn-(0.2-1.0)Mn (wt.%). The adjustment range needs to be judged according to the actual production. If there is no composition deviation, it can be omitted.

[0050] d) High-temperature stepwise static impurity removal: Keep the mixed metal liquid at a temperature of 850℃±50℃ for 110-120 minutes, then remove the slag (flux, impurity sediment, etc.) at the bottom of the crucible and start cooling;

[0051] The mixed metal liquid is the qualified metal liquid obtained after the secondary furnace component test in step C);

[0052] When the surface begins to solidify, wait for 40-50 minutes, raise the temperature to 700℃±50℃, take the molten sample for the third furnace composition test to ensure that the alloy composition is within the set range (Mg-(2.5-3.5)Al-(0.6-1.4)Zn-(0.2-1.0)Mn (wt.%));

[0053] e) Casting in a semi-continuous casting system: Raise the melt temperature to 750-760°C, close the furnace cover, press high-purity argon gas into the liquid guide tube to start pouring, keep the temperature of the tundish (a container for storing the liquid part of the magnesium alloy during the process from liquid to solidification in the semi-continuous casting system) at 690-700°C, keep the ingot pulling speed of the casting machine (a traction device in the semi-continuous casting system, which pulls the semi-continuous cast rod) at 50-200mm / min, and keep the cooling water flow at 3-5m 3 / h, to obtain semi-continuous casting rods;

[0054] f) Appearance inspection and material collection: After the semi-continuous cast rods are peeled, visual inspection is carried out to ensure that there is no looseness, shrinkage cavity inclusions, etc. visible to the naked eye. The materials are cut and set aside according to the requirements of the plastic forming process, i.e., AZ31 alloy ingots.

[0055] The No. 5 flux is MgCl2=46-54%, KCl=29-33%, NaCl=17-21%, water-insoluble matter≤1.5%, moisture≤1%; the protective gas is argon (99.999%).

[0056] The step 4 is specifically as follows:

[0057] a) Homogenization treatment: The peeled high-quality AZ31 alloy ingot is homogenized in a protective atmosphere (such as high-purity argon, etc.), the homogenization temperature is 400-420°C, the homogenization time is 20-30h, and the cooling method is water quenching;

[0058] b) Plastic forming: The high quality AZ31 alloy ingot is subjected to thermomechanical treatment by plastic forming methods such as extrusion, forging and rolling.

[0059] For extrusion forming, the preheating temperature of the billet is 420℃±20℃, the extrusion die temperature is 420℃±20℃, and the insulation is 8h; the extrusion feed speed is 0.6mm / s, the extrusion barrel temperature is set at 420℃±20℃, and the extrusion ratio is set at 57.6.

[0060] And the billet preheating temperature, extrusion die temperature and extrusion barrel temperature are the same.

[0061] At this point, the preparation of fatigue-resistant AZ31 deformed alloy, namely fatigue-resistant Mg-Al magnesium alloy, has been completed.

[0062] Beneficial effects of the present invention:

[0063] The invention provides a method for preparing a Mg-Al deformable magnesium alloy with both high mechanical properties and fatigue resistance at low cost, which has good economic applicability.

[0064] The Mg-Al deformable magnesium alloy is prepared by a purification smelting method of "raw material impurity removal + process impurity control". Specifically, it includes the selection of purified raw materials, such as the use of laboratory-made pure magnesium, pure aluminum, pure zinc and anhydrous manganese chloride with higher purity; purification smelting process control, such as the use of graphite crucibles to avoid excessive introduction of Fe impurities, the use of flux and high-temperature standing to remove oxides; semi-continuous casting and solidification of ingots, which can better avoid casting defects such as looseness, shrinkage and macro segregation, and ensure the quality of subsequent plastic forming ingots.

[0065] The high-quality magnesium alloy can effectively reduce the number of oxide inclusions, reduce the total volume of oxide inclusions by one order of magnitude, and at the same time increase the fatigue strength by more than 30 MPa, effectively improving fatigue resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 It is the fatigue fracture and fatigue crack initiation source of AZ31 magnesium alloy.

[0067] (a) Macroscopic morphology of fatigue fracture of AZ31 magnesium alloy. ①, ② and ③ in the figure are three typical fracture areas of AZ31 magnesium alloy after subjected to uniaxial tensile load of R=0.1, ①: crack initiation zone, ②: crack propagation zone, ③: instantaneous fracture zone; (b) cleavage surface morphology of instantaneous fracture zone; (c) dimple morphology of instantaneous fracture zone; (d) morphology of crack propagation zone; (e) morphology of crack initiation zone; (f) macroscopic morphology of crack initiation zone; (g) enlarged view of the white frame in Figure (f); (h) inclusion composition map in Figure (g).

[0068] Figure 2 Schematic diagram of the graphite parts arrangement for the magnesium purification process.

[0069] Figure 3 Schematic diagram of heating curves in different temperature zones.

[0070] Figure 4 Schematic diagram of fatigue-resistant AZ31 magnesium alloy; (a) 3D reconstructed CT image of internal inclusions; (b) inclusion equivalent diameter-frequency distribution diagram.

[0071] Figure 5 This is the small sample lifting method diagram of the fatigue limit of fatigue-resistant AZ31 magnesium alloy under uniaxial tension-tension (R=0.1).

[0072] Figure 6 This is the SN curve of uniaxial tension-tension fatigue (R=0.1) of fatigue-resistant AZ31 deformed magnesium alloy Example 3.

[0073] Figure 7 (a) 3D reconstructed CT image of internal inclusions in common commercial extruded AZ31 magnesium alloy; (b) inclusion equivalent diameter-frequency distribution diagram.

[0074] Figure 8Schematic diagram of the arrangement of graphite parts in the process of remelting high-purity crystalline magnesium to obtain high-purity magnesium ingots in steps (e)-(j).

[0075] Fig. 9 The surface metallographic structure, texture, texture strength and uniaxial tensile mechanical properties of the fatigue-resistant Mg-Al magnesium alloy are shown. DETAILED DESCRIPTION

[0076] The present invention will be further described in detail below in conjunction with the accompanying drawings.

[0077] From the fatigue fracture of AZ31 magnesium alloy ( Figure 1 ) It can be seen that the fatigue fracture of magnesium alloy is a typical type I fracture, showing a typical three-region morphology, namely the crack initiation zone, the crack propagation zone and the instantaneous fracture zone. There are a small number of cleavage planes and a large number of dimples in the instantaneous fracture zone, which is a typical quasi-cleavage fracture. There are a large number of slip planes, a small number of twins and some inclusions in the morphology near the crack initiation source in the crack initiation zone. The slip system and twins near the inclusions coordinate the grain deformation at the beginning of fatigue loading, but under the influence of inclusions with high stress concentration, fatigue cracks initiate preferentially at the grains near the inclusions. At the crack initiation source, carbon, nitrogen and oxygen inclusions with a size of 20μm can be observed on the surface of the specimen ( Figure 1 ), is the main factor inducing crack initiation. Therefore, reducing the number of inclusions and avoiding their distribution on the surface is one of the optional paths to improve the fatigue resistance of Mg-Al magnesium alloys.

[0078] A method for preparing a fatigue-resistant Mg-Al deformation alloy comprises the following steps:

[0079] Step 1: Preparation of alloy raw materials and purity control of auxiliary materials:

[0080] (a) In accordance with Figure 2 Assemble the graphite parts in the order shown, a1 uses a 50mm long graphite part, a2-a13 uses a 100mm long graphite part, b1 and b3 use a graphite blind plate, b2 uses a seven-hole graphite plate and adds a layer of 200-mesh metal tungsten mesh, and finally put the raw magnesium material into the evaporation zone, i.e. a6 graphite part;

[0081] The components are connected in sequence;

[0082] (b) The assembled graphite parts are placed into the corundum tube of the electric furnace and sealed with a flange;

[0083] (c) Turn on the vacuum pump switch, and when the vacuum degree in the corundum tube reaches below 10Pa, the circuit heating can be turned on. The heating curves of the three temperature zones are arranged as follows:

[0084] (d) After heating is completed, wait for the electric furnace to cool naturally to below 50°C, close the vacuum valve and vacuum pump, then open the electric furnace flange valve to allow the pressure in the corundum tube to return to normal pressure, finally punch the flange to take out the graphite parts, and take out the purified high-purity crystalline magnesium from under the graphite blind plate b3 in the condensation area.

[0085] (e) In accordance with Figure 8 Assemble graphite parts in the order shown, a13 uses a 50 mm long graphite part, a1-a12 use a 100 mm long graphite part, b1 and b3 use a graphite blind plate, and b2 uses a seven-hole graphite plate, and high-purity crystalline magnesium is loaded into the raw material area;

[0086] (f) Place the assembled graphite parts into the corundum tube of the electric furnace and seal it with a flange; turn on the vacuum pump switch and close the vacuum valve when the vacuum degree reaches below 50Pa;

[0087] (g) Open the argon valve and gas flow meter, and when the pressure in the tube returns to normal pressure, close the argon valve;

[0088] (h) Repeat (f) and (g) 2-3 times to complete the gas washing, then open the argon valve and the gas outlet at the other end of the furnace tube, adjust the flow meter flow rate to 150sccm, and maintain the micro-flow state in the tube;

[0089] (i) The upper and middle temperature zones of the electric furnace were set to 900°C (raw material zone), the lower temperature zone (ingot zone) was set to 830°C, the heating rate was 10°C / min, and the temperature was kept for 600 min;

[0090] (j) After the insulation is completed, the electric furnace needs to be cooled naturally to below 50°C, and then the argon valve can be closed, the flange can be opened and the graphite parts can be removed to obtain a high-purity magnesium alloy net dense ingot.

[0091] (k) The alloy composition is designed to be Mg-(2.5-3.5)Al-(0.6-1.4)Zn-(0.2-1.0)Mn (wt.%), using laboratory-made high-purity magnesium (i.e., high-purity magnesium alloy net dense ingot) (99.98%), pure aluminum (99.85%), pure zinc (99.995%), and anhydrous manganese chloride (98.38%, water-insoluble matter ≤0.005); the flux used is No. 5 flux (MgCl2=46-54%, KCl=29-33%, NaCl=17-21%, water-insoluble matter ≤1.5%, moisture ≤1%); the protective gas is argon (99.999%).

[0092] Step 2: Using a purified magnesium alloy semi-continuous casting system:

[0093] The crucible is a high-purity and high-density graphite crucible (volume density 1.82-1.85g / cm 3, thermal conductivity 85W / (m·K), ash content 500ppm, purified ash content 11ppm, particle size 8-11μm); the liquid guide tube is made of 304 stainless steel; the crystallizer uses graphite inner wall; the cooling medium is industrial water;

[0094] The purpose of this step is to prepare the crucible, liquid guide tube, crystallizer and cooling medium for step 3.

[0095] Step 3: Gradually adjust the temperature according to the following smelting process and add materials to adjust the composition in time

[0096] a) Stepwise heating and protection standby: The debugged and purified magnesium alloy semi-continuous casting system is heated to 300℃±50℃ and kept warm for 2h. Argon is passed through the exposed area of ​​the graphite crucible for protection and the temperature is continued to rise to 600℃±50℃ and kept warm for 1h. Then the temperature is raised to 835℃±50℃ for standby use. The subsequent processes are all carried out under a mixed protective atmosphere of high-purity argon + high-purity CO2 + sulfur hexafluoride, where the flow rate ratio of CO2 to SF6 is 100:1.

[0097] b) Testing of main alloy melt: According to the alloy ratio and alloy element burnout rate, first put pure magnesium into the crucible and wait for it to be fully melted. Then set the temperature to 855℃±50℃. Then put pure zinc and pure aluminum ingots into the crucible, stir them thoroughly and add anhydrous MnCl2 (please place the materials gently to avoid damaging the graphite crucible).

[0098] According to the ratio of Mg-(2.5-3.5)Al-(0.6-1.4)Zn-(0.2-1.0)Mn (wt.%);

[0099] After all the input materials are melted, stir them in the solution for about 10-15 minutes with argon protection. Use No. 5 flux with a mass ratio of about 1-3% of the total melt mass to refine at 740-750℃ for 10-15 minutes, stir them in the solution with argon, and take the melt sample for the first pre-furnace composition test.

[0100] c) Adjustment of alloy composition: Add pure magnesium, pure zinc, pure aluminum, and anhydrous MnCl2 to adjust the alloy composition, and then conduct secondary refining, using No. 5 flux with a mass ratio of about 1-3% of the total melt mass to refine at 740-750℃, and stir the solution with argon for about 10-15 minutes. Take a sample of the molten liquid for a second furnace pre-composition test to ensure that the micro-element alloy composition is within the set range ((0.2-1.0)Mn (wt.%)). This step is to avoid the step of adjusting the alloy composition in step b) if it does not reach the preset composition. The composition is based on the above-mentioned design composition, Mg-(2.5-3.5)Al-(0.6-1.4)Zn-(0.2-1.0)Mn (wt.%). The adjustment range needs to be judged according to the actual production. If there is no composition deviation, it can be omitted.

[0101] d) High-temperature stepwise static removal of impurities: Keep the mixed metal liquid at a temperature of 850℃±50℃ for 110-120 minutes, then remove the slag (flux, impurity sediment, etc.) at the bottom of the crucible and start cooling.

[0102] The mixed molten metal is the qualified molten metal obtained after the secondary furnace composition test in step C);

[0103] When the surface begins to solidify, wait for 40-50 minutes, raise the temperature to 700℃±50℃, take the molten sample for the third furnace composition test to ensure that the alloy composition is within the set range (Mg-(2.5-3.5)Al-(0.6-1.4)Zn-(0.2-1.0)Mn (wt.%)).

[0104] e) Crystallizer casting: Raise the melt temperature to 750-760℃, close the furnace cover, press high-purity argon gas into the liquid guide tube to start pouring, keep the temperature of the tundish (a container for storing the liquid part of the magnesium alloy during the process from liquid to solidification in the semi-continuous casting system) at 690-700℃, keep the ingot pulling speed of the casting machine (a traction device in the semi-continuous casting system, which pulls the semi-continuous cast rod) at 50-200mm / min, and keep the cooling water flow at 3-5m 3 / h, and obtain semi-continuous cast rods.

[0105] f) Appearance inspection and material collection: After the semi-continuous casting rods are peeled, visual inspection is carried out to ensure that there is no looseness, shrinkage holes, etc. visible to the naked eye. The materials are cut and set aside according to the requirements of the plastic forming process.

[0106] Step 4: Plastic forming

[0107] a) Homogenization treatment: The peeled high-quality AZ31 alloy ingot is homogenized in a protective atmosphere (such as high-purity argon, etc.), the homogenization temperature is 400-420°C, the homogenization time is 20-30h, and the cooling method is water quenching.

[0108] b) Plastic forming: The homogenized ingot of the multi-component microalloyed Mg-Al alloy is subjected to thermomechanical treatment by plastic forming methods such as extrusion, forging and rolling.

[0109] For example, for extrusion forming, the preheating temperature of the billet is 420℃±20℃, the extrusion die temperature is 420℃±20℃, and the insulation is 8h; the extrusion feed speed is 0.6mm / s, the extrusion barrel temperature is set at 420℃±20℃, and the extrusion ratio is set at 57.6.

[0110] And the billet preheating temperature, extrusion die temperature and extrusion barrel temperature are the same.

[0111] At this point, the preparation of fatigue-resistant AZ31 deformation alloy has been completed.

[0112] Implementation Case 1

[0113] The designed alloy composition is: Mg-3Al-1Zn-1Mn (wt.%).

[0114] Fatigue-resistant AZ31 wrought magnesium alloy preparation system

[0115] (1) A pure smelting preparation system is used, the crucible is a high-purity and high-density graphite crucible (volume density 1.82-1.85 g / cm3, thermal conductivity 85 W / (m·K), ash content 500 ppm, purified ash content 11 ppm, particle size 8-11 μm); the liquid guide tube is made of 304 stainless steel; the crystallizer has a graphite inner wall; and the cooling medium is industrial water.

[0116] (2) The raw materials are high-purity magnesium (99.98%), pure aluminum (99.85%), pure zinc (99.995%), and anhydrous manganese chloride (98.38%, water-insoluble matter ≤ 0.005) prepared in the laboratory; the flux is No. 5 flux (MgCl2 = 46-54%, KCl = 29-33%, NaCl = 17-21%, water-insoluble matter ≤ 1.5%, moisture ≤ 1%); the protective gas is argon (99.999%).

[0117] Preparation process of fatigue-resistant AZ31 wrought magnesium alloy

[0118] (1) The fully debugged clean magnesium alloy semi-continuous casting system was heated to 300°C and kept warm for 2 h. Argon gas was passed through the exposed area of ​​the graphite crucible to continue heating to 600°C and kept warm for 1 h. The temperature was then raised to 750°C for standby use. The subsequent processes were all carried out under a mixed protective atmosphere of high-purity argon + high-purity CO2 + sulfur hexafluoride, where the flow rate ratio of CO2 to SF6 was 100:1.

[0119] (2) According to the alloy proportion composition and alloy element burnout rate of 200kg of Mg-3Al-1Zn-1Mn (wt.%), first put pure magnesium, pure zinc and pure aluminum ingots into the crucible. When adding materials, they need to be placed gently to avoid damaging the graphite crucible. Keep warm at 740-750℃ to ensure that all the input materials are melted. After stirring the solution with argon for about 10-15 minutes, add anhydrous MnCl2 and wait for it to melt. Use about 2kg of No. 5 flux to refine at 740-750℃ for 10-15 minutes. Stir the solution with argon and take the melt sample for the first pre-furnace composition test.

[0120] (3) Add pure magnesium, pure zinc, pure aluminum, and anhydrous MnCl2 to adjust the alloy composition, and then conduct secondary refining, so that about 2 kg of No. 5 flux is refined at 740-750 ° C, and argon is used to stir the solution for about 10-15 minutes. Take the melt sample for the second furnace pre-composition test to ensure that the micro-element alloy composition is within the set range, Mg-3Al-1Zn-1Mn (wt.%).

[0121] (4) Keep the mixed metal liquid at 850°C for 110-120 minutes, then remove the slag (flux, impurity sediment, etc.) at the bottom of the crucible and start cooling. When the surface begins to solidify, wait for 40-50 minutes and raise the temperature to 700°C. Take the melt sample for the third furnace composition test to ensure that the micro-element alloy composition is within the set range, Mg-3Al-1Zn-1Mn (wt.%).

[0122] (5) Raise the melt temperature to 750-760°C, close the furnace cover, pressurize the melt high-purity argon gas into the liquid guide pipe to start casting in the crystallizer. The tundish temperature is maintained at 690-700°C, the casting machine ingot pulling speed is maintained at 50-200mm / min, and the cooling water flow rate is maintained at 3-5m 3 / h.

[0123] (6) The ingot is peeled and visually inspected to ensure that there is no looseness or shrinkage cavity inclusions visible to the naked eye. It is then cut into Φ203mm×225mm bars according to the extrusion forming process for later use.

[0124] (7) The Φ203 mm×225 mm fatigue-resistant AZ31 magnesium alloy rod prepared above was homogenized in an argon protective atmosphere with homogenization parameters of 400°C, 24 h, and room temperature water quenching.

[0125] (8) An 1800T horizontal extruder is used to extrude the Φ203mm×225mm rod after homogenization treatment. The extruded profile is a plate with a cross-sectional size of 220×3mm. The billet preheating temperature is 420°C, the extrusion die temperature is 420°C, the extrusion feed speed is 0.6mm / s, the extrusion barrel temperature is set to 420°C, the extrusion ratio is set to 57.6, and the extruded material is pulled by a traction machine with a traction force of about 200N.

[0126] Test on the number and distribution of inclusions in fatigue-resistant AZ31 wrought magnesium alloy

[0127] The fatigue-resistant Mg-3Al-1Zn-1Mn (wt.%) deformed plate was characterized by CT scanning. The characterization results are shown in Figure 4 The selected area is a Φ1mm×2mm cylinder with a resolution of 2μm (the subsequent CT parameters are the same as this parameter). This method can control the number of inclusions in AZ31 magnesium alloy to 489 / mm3 The volume percentage of inclusions is 0.0627%.

[0128] Implementation Case 2

[0129] The designed alloy composition is: Mg-3Al-1Zn-1Mn (wt.%).

[0130] Fatigue-resistant AZ31 wrought magnesium alloy preparation system

[0131] (1) A pure smelting preparation system is used, the crucible is a high-purity and high-density graphite crucible (volume density 1.82-1.85 g / cm3, thermal conductivity 85 W / (m·K), ash content 500 ppm, purified ash content 11 ppm, particle size 8-11 μm); the liquid guide tube is made of 304 stainless steel; the crystallizer has a graphite inner wall; and the cooling medium is industrial water.

[0132] (2) The raw materials are high-purity magnesium (99.98%), pure aluminum (99.85%), pure zinc (99.995%), and anhydrous manganese chloride (98.38%, water-insoluble matter ≤ 0.005) prepared in the laboratory; the flux is No. 5 flux (MgCl2 = 46-54%, KCl = 29-33%, NaCl = 17-21%, water-insoluble matter ≤ 1.5%, moisture ≤ 1%); the protective gas is argon (99.999%).

[0133] Preparation process of fatigue-resistant AZ31 wrought magnesium alloy

[0134] (1) The fully debugged clean magnesium alloy semi-continuous casting system was heated to 300°C and kept warm for 2 h. Argon gas was passed through the exposed area of ​​the graphite crucible to continue heating to 600°C and kept warm for 1 h. The temperature was then raised to 750°C for standby use. The subsequent processes were all carried out under a mixed protective atmosphere of high-purity argon + high-purity CO2 + sulfur hexafluoride, where the flow rate ratio of CO2 to SF6 was 100:1.

[0135] (2) According to the alloy proportion composition and alloy element burnout rate of 200kg of Mg-3Al-1Zn-1Mn (wt.%), first put pure magnesium, pure zinc and pure aluminum ingots into the crucible. When adding materials, they need to be placed gently to avoid damaging the graphite crucible. Keep warm at 740-750℃ to ensure that all the input materials are melted. After stirring the solution with argon for about 10-15 minutes, add anhydrous MnCl2 and wait for it to melt. Use about 2kg of No. 5 flux to refine at 740-750℃ for 10-15 minutes. Stir the solution with argon and take the melt sample for the first pre-furnace composition test.

[0136] (3) Add pure magnesium, pure zinc, pure aluminum, and anhydrous MnCl2 to adjust the alloy composition, and then conduct secondary refining, refining about 2 kg of No. 5 flux at 740-750 ° C, stirring the solution with argon for about 10-15 minutes. Take the melt sample for the second furnace composition test to ensure that the micro-element alloy composition is within the set range.

[0137] (4) Keep the mixed metal liquid at 850℃ for 110-120 minutes, then remove the slag (flux, impurity sediment, etc.) at the bottom of the crucible and start cooling. When the surface begins to solidify, wait for 40-50 minutes and raise the temperature to 700℃. Take the melt sample for the third furnace composition test to ensure that the micro-element alloy composition is within the set range.

[0138] (5) Raise the melt temperature to 750-760°C, close the furnace cover, pressurize the melt high-purity argon gas into the liquid guide pipe to start casting in the crystallizer. The tundish temperature is maintained at 690-700°C, the casting machine ingot pulling speed is maintained at 50-200mm / min, and the cooling water flow rate is maintained at 3-5m 3 / h.

[0139] (6) The ingot is peeled and visually inspected to ensure that there is no looseness or shrinkage cavity inclusions visible to the naked eye. It is then cut into Φ203mm×225mm bars according to the extrusion forming process for later use.

[0140] (7) The prepared Φ203 mm×225 mm high-quality AZ31 magnesium alloy rod was homogenized in an argon protective atmosphere at 400°C for 24 h and then quenched in water at room temperature.

[0141] (8) An 1800T horizontal extruder is used to extrude the Φ203mm×225mm rod after homogenization treatment. The extruded profile is a plate with a cross-sectional size of 220×3mm. The billet preheating temperature is 420°C, the extrusion die temperature is 420°C, the extrusion feed speed is 0.6mm / s, the extrusion barrel temperature is set to 420°C, the extrusion ratio is set to 57.6, and the extruded material is pulled by a traction machine with a traction force of about 200N.

[0142] Fatigue resistance AZ31 deformation alloy performance test

[0143] The fatigue performance of the Mg-3Al-1Zn-1Mn (wt.%) deformed plate was tested by uniaxial tension-tension fatigue (R=0.1) test method and its fatigue limit (such as Figure 5 The room temperature uniaxial tensile mechanical property test method was used to test the mechanical properties of the plate at room temperature. The test results are shown in Table 1. It can be seen that this method can achieve fatigue-resistant AZ31 deformed magnesium alloy with both high mechanical properties and fatigue resistance at a low cost.

[0144] Table 1 Mechanical properties and fatigue properties of fatigue-resistant AZ31 wrought magnesium alloy Example 2

[0145]

[0146] Implementation Case 3

[0147] The designed alloy composition is: Mg-3Al-1Zn-1Mn (wt.%).

[0148] Fatigue-resistant AZ31 wrought magnesium alloy preparation system

[0149] (1) A pure smelting preparation system is used, the crucible is a high-purity and high-density graphite crucible (volume density 1.82-1.85 g / cm3, thermal conductivity 85 W / (m·K), ash content 500 ppm, purified ash content 11 ppm, particle size 8-11 μm); the liquid guide tube is made of 304 stainless steel; the crystallizer has a graphite inner wall; and the cooling medium is industrial water.

[0150] (2) The raw materials are high-purity magnesium (99.98%), pure aluminum (99.85%), pure zinc (99.995%), and anhydrous manganese chloride (98.38%, water-insoluble matter ≤ 0.005) prepared in the laboratory; the flux is No. 5 flux (MgCl2 = 46-54%, KCl = 29-33%, NaCl = 17-21%, water-insoluble matter ≤ 1.5%, moisture ≤ 1%); the protective gas is argon (99.999%).

[0151] Preparation process of fatigue-resistant AZ31 wrought magnesium alloy

[0152] (1) The fully debugged clean magnesium alloy semi-continuous casting system was heated to 300°C and kept for 2 hours. The exposed area of ​​the graphite crucible was heated to 600°C and kept for 1 hour under argon protection, and then heated to 750°C for standby use. The subsequent processes were all carried out under a mixed protective atmosphere of high-purity argon + high-purity CO2 + sulfur hexafluoride, where the flow rate ratio of CO2 to SF6 was 100:1.

[0153] (2) According to the alloy proportion composition and alloy element burnout rate of 200kg of Mg-3Al-1Zn-1Mn (wt.%), first put pure magnesium, pure zinc and pure aluminum ingots into the crucible. When adding materials, they need to be placed gently to avoid damaging the graphite crucible. Keep warm at 740-750℃ to ensure that all the input materials are melted. After stirring the solution with argon for about 10-15 minutes, add anhydrous MnCl2 and wait for it to melt. Use about 2kg of No. 5 flux to refine at 740-750℃ for 10-15 minutes. Stir the solution with argon and take the melt sample for the first pre-furnace composition test.

[0154] (3) Add pure magnesium, pure zinc, pure aluminum, and anhydrous MnCl2 to adjust the alloy composition, and then conduct secondary refining, refining about 2 kg of No. 5 flux at 740-750 ° C, stirring the solution with argon for about 10-15 minutes. Take the melt sample for the second furnace composition test to ensure that the micro-element alloy composition is within the set range.

[0155] (4) Keep the mixed metal liquid at 850℃ for 110-120 minutes, then remove the slag (flux, impurity sediment, etc.) at the bottom of the crucible and start cooling. When the surface begins to solidify, wait for 40-50 minutes and raise the temperature to 700℃. Take the melt sample for the third furnace composition test to ensure that the micro-element alloy composition is within the set range.

[0156] (5) Raise the melt temperature to 750-760°C, close the furnace cover, pressurize the melt high-purity argon gas into the liquid guide pipe to start casting in the crystallizer. The tundish temperature is maintained at 690-700°C, the casting machine ingot pulling speed is maintained at 50-200mm / min, and the cooling water flow rate is maintained at 3-5m 3 / h.

[0157] (6) The ingot is peeled and visually inspected to ensure that there is no looseness or shrinkage cavity inclusions visible to the naked eye. It is then cut into Φ203mm×225mm bars according to the extrusion forming process for later use.

[0158] (7) The prepared Φ203 mm×225 mm high-quality AZ31 magnesium alloy rod was homogenized in an argon protective atmosphere at 400°C for 24 h and then quenched in water at room temperature.

[0159] (8) An 1800T horizontal extruder is used to extrude the Φ203mm×225mm rod after homogenization treatment. The extruded profile is a plate with a cross-sectional size of 220×3mm. The billet preheating temperature is 420°C, the extrusion die temperature is 420°C, the extrusion feed speed is 0.6mm / s, the extrusion barrel temperature is set to 420°C, the extrusion ratio is set to 57.6, and the extruded material is pulled by a traction machine with a traction force of about 200N.

[0160] Fatigue resistance of AZ31 wrought magnesium alloy performance test

[0161] On the basis of 128MPa fatigue limit, a stress gradient of 10MPa was set, and the SN curve test of the above Mg-3Al-1Zn-1Mn (wt.%) deformed plate was carried out by uniaxial tension-tension (R=0.1) fatigue test method. The test results are as follows Figure 4 As shown. The SN curve fitting result is: σ r =-15.8lgN+236.6, and at the same time, under higher stress gradients (such as 138, 148, 158MPa), there are N=107 Cyclic loading without fatigue fracture.

[0162] Comparative Cases

[0163] The alloy composition of the comparative case is: Mg-3Al-1Zn-1Mn (wt.%), which is a common commercial extruded AZ31 magnesium alloy.

[0164] Test on the number and distribution of inclusions in common commercial Mg-Al deformation alloys

[0165] The above-mentioned Mg-3Al-1Zn-1Mn (wt.%) common commercial extruded AZ31 magnesium alloy was characterized by CT tomography. The characterization results are shown in Figure 7 As shown in the figure, it can be seen that the number of internal inclusions in the ordinary commercial extruded AZ31 magnesium alloy that has not passed the "raw material impurity removal + process impurity control" is 7486 / mm 3 , the volume percentage of inclusions is 0.45%.

[0166] The fatigue limit test of the above Mg-3Al-1Zn-1Mn (wt.%) deformed sheet was carried out by uniaxial tension-tension fatigue (R=0.1) test method. The test results are shown in Table 2. It can be seen that the high-quality AZ31 deformed magnesium alloy after "raw material impurity removal + process impurity control" has higher mechanical properties and fatigue resistance than the ordinary commercial extruded AZ31 deformed alloy.

[0167] Table 2 Fatigue limit of common commercial AZ31 extruded magnesium alloy comparative example 1

[0168]

[0169] like Fig. 9 As shown, the fatigue resistance of the material of the vegetation in this application mainly has two aspects. First, under the same stress ratio, the same number of cycles is set. This time, N=10^7 is set for comparison, and the fatigue limit is compared. The one with a higher fatigue limit has better fatigue performance.

[0170] Second, under the same stress ratio, set the same stress amplitude and compare their fatigue life. For example, fatigue loading can be set at 160MPa. By comparing the number of cycles when they break, the longer the fatigue life, the better the fatigue performance.

[0171] This application uses the first method. By comparing the implementation cases 2 and 3, it can be found that the fatigue limit of the magnesium alloy prepared by the "raw material removal and process control" scheme is nearly 40MPa higher than that of ordinary commercial magnesium alloys (when the number of cycles N=10^7 and the stress ratio R=0.1).

Claims

1. A method for improving the fatigue strength of a deformed Mg-Al magnesium alloy, characterized in that: The steps include: Step 1: Select alloy raw materials Mg, Al, Zn and Mn, in which the Al content is 2.5-3.5%, the Zn content is 0.6-1.4%, the Mn content is 0.2-1.0, and the balance is Mg. Step 2: placing the alloy raw material into a semi-continuous casting system for casting to obtain a semi-continuous cast rod, and performing a peeling process on the semi-continuous cast rod to obtain an AZ31 alloy ingot; Step 3: Plastically forming the AZ31 alloy ingot obtained in step 2 to obtain a fatigue-resistant Mg-Al magnesium alloy.

2. A method for improving fatigue strength of deformed Mg-Al magnesium alloy according to claim 1, characterized in that: The step 1 is specifically as follows: (a) Assembling graphite parts; placing raw magnesium to be purified into the graphite parts; (b) The assembled graphite parts are placed into the corundum tube of the electric furnace and sealed with a flange; (c) Turn on the vacuum pump switch, and when the vacuum degree in the corundum tube reaches below 10Pa, start the circuit heating; (d) After heating is completed, wait for the electric furnace to cool naturally to below 50° C., close the vacuum valve and vacuum pump, then open the electric furnace flange valve to return the pressure in the corundum tube to normal pressure, finally punch the flange to take out the graphite part, and take out the purified high-purity crystalline magnesium; (e) assembling a graphite piece, and loading high-purity crystalline magnesium into a raw material area in the graphite piece; (f) Place the assembled graphite parts into the corundum tube of the electric furnace and seal it with a flange; turn on the vacuum pump switch and close the vacuum valve when the vacuum degree reaches below 50Pa; (g) Open the argon valve and gas flow meter, and when the pressure in the tube returns to normal pressure, close the argon valve; (h) Repeat (f) and (g) 2-3 times to complete the gas washing, then open the argon valve and the gas outlet at the other end of the furnace tube, adjust the flow rate of the flow meter to maintain the micro-flow state in the tube; (i) The upper and middle temperature zones of the electric furnace were set to 900°C (raw material zone), the lower temperature zone (ingot zone) was set to 830°C, the heating rate was 10°C / min, and the temperature was kept for 600 min; (j) After the insulation is completed, the electric furnace needs to be cooled naturally to below 50°C, and then the argon valve can be closed, the flange can be opened and the graphite parts can be removed to obtain a high-purity magnesium alloy net dense ingot; (k) Using laboratory-made high-purity magnesium, i.e., high-purity magnesium alloy net dense ingots of pure aluminum, pure zinc, and anhydrous manganese chloride; the alloy is designed according to the composition of Mg-(2.5-3.5)Al-(0.6-1.4)Zn-(0.2-1.0)Mn (wt.%).

3. A method for improving fatigue strength of deformed Mg-Al magnesium alloy according to claim 2, characterized in that: In said (a): Arrange the graphite parts in the order of a1-a13, with a1 using a 50mm long graphite part and a2-a13 using a 100mm long graphite part; The graphite blind plate b1 is placed between the graphite piece a5 and the graphite piece a6, the seven-hole graphite plate b2 is placed between the graphite piece a8 and the graphite piece a9, and the graphite blind plate b3 is placed between the graphite piece a10 and the graphite piece a11; The graphite parts are connected by internal and external threads, and are cylindrical hollow structures; Put the raw magnesium to be purified into the a6 graphite part; Graphite piece a6 is the evaporation zone, graphite piece a6 to graphite piece a9 are the gas phase channels, and graphite piece a10 is the condensation zone; The evaporation zone is the lower temperature zone, the graphite parts a7 and a8 of the gas phase channel are located in the middle temperature zone, and the graphite part a9 and the condensation zone are located in the upper temperature zone.

4. The method for improving fatigue strength of deformed Mg-Al magnesium alloy according to claim 2, characterized in that: In (e), the graphite pieces are arranged in the order of a1-a13, and a13 uses a 50 mm long graphite piece, and a1-a12 use a 100 mm long graphite piece; The graphite blind plate b1 is placed between the graphite piece a4 and the graphite piece a5, the seven-hole graphite plate b2 is placed between the graphite piece a6 and the graphite piece a5, and the graphite blind plate b3 is placed between the graphite piece a10 and the graphite piece a11; The graphite parts are connected by internal and external threads, and are cylindrical hollow structures; Graphite parts a5 and a6 are ingot areas, and graphite parts a7 to a10 are raw material areas.

5. The method for improving fatigue strength of deformed Mg-Al magnesium alloy according to claim 1, characterized in that: The step 2 is specifically as follows: The semi-continuous casting system includes a crucible, a liquid guide tube and a crystallizer connected in sequence. The crucible is a high-purity and high-density graphite crucible with a volume density of 1.82-1.85g / cm 3 , thermal conductivity 85W / (m·K), ash content 500ppm, purified ash content 11ppm, particle size 8-11μm; the liquid guide tube is made of 304 stainless steel; the crystallizer adopts graphite inner wall; the cooling medium is industrial water.

6. The method for improving fatigue strength of deformed Mg-Al magnesium alloy according to claim 1, characterized in that: The step 3 is specifically as follows: a) The temperature of the fully debugged and purified magnesium alloy semi-continuous casting system is raised to 300℃±50℃ for insulation, and the exposed area of ​​the graphite crucible is heated to 600℃±50℃ for insulation through argon protection, and then raised to 835℃±50℃ for standby use. The subsequent processes are all carried out under a mixed protective atmosphere of high-purity argon + high-purity CO2 + sulfur hexafluoride, where the flow rate ratio of CO2 to SF6 is 100:1; b) According to Mg-(2.5-3.5)Al-(0.6-1.4)Zn-(0.2-1.0)Mn (wt.%), the alloy ratio composition and alloy element burnout rate are carried out. First, high-purity magnesium is put into a crucible and after being fully melted, the temperature is set to 855°C ± 50°C, and then pure zinc and pure aluminum ingots are put into the crucible, and anhydrous MnCl2 is added after being fully stirred; After all the input materials are melted, stir them in the solution for about 10-15 minutes with argon protection; use No. 5 flux with a mass ratio of about 1-3% of the total melt mass to refine at 740-750℃ for 10-15 minutes, stir them in the solution with argon, and take the melt sample for the first pre-furnace composition test; c) adding pure magnesium, pure zinc, pure aluminum, and anhydrous MnCl2 to adjust the alloy composition, and then performing secondary refining, using No. 5 flux with a mass ratio of about 1-3% of the total melt mass at 740-750° C., and stirring the solution with argon for about 10-15 minutes; taking a sample of the melt for a second furnace pre-composition test to ensure that the micro-element alloy composition is within the set range ((0.2-1.0)Mn (wt.%)); The composition is based on the above design composition: Mg-(2.5-3.5)Al-(0.6-1.4)Zn-(0.2-1.0)Mn (wt.%). The adjustment range needs to be judged according to the actual production. If there is no composition deviation, it can be omitted. d) Keep the mixed metal liquid at a temperature of 850°C ± 50°C for 110-120 minutes, then remove the slag at the bottom of the crucible and start cooling; The mixed metal liquid is the qualified metal liquid obtained after the secondary furnace component test in step C); When the surface begins to solidify, wait for 40-50 minutes, raise the temperature to 700℃±50℃, take the molten sample for the third furnace composition test to ensure that the alloy composition is within Mg-(2.5-3.5)Al-(0.6-1.4)Zn-(0.2-1.0)Mn (wt.%); e) Raise the melt temperature to 750-760℃, close the furnace cover, pressurize the melt high-purity argon gas into the liquid guide tube to start pouring, keep the tundish temperature at 690-700℃, keep the casting machine ingot pulling speed at 50-200mm / min, and keep the cooling water flow at 3-5m 3 / h, to obtain semi-continuous casting rods; f) After the semi-continuous cast rod is peeled, a visual inspection is performed to determine if there is no looseness or shrinkage cavity inclusions visible to the naked eye. The material is cut and set aside according to the requirements of the plastic forming process, i.e., the AZ31 alloy ingot.

7. A method for improving fatigue strength of deformed Mg-Al magnesium alloy according to claim 6, characterized in that: The No. 5 flux is MgCl2=46-54%, KCl=29-33%, NaCl=17-21%, water-insoluble matter≤1.5%, moisture≤1%; the protective gas is argon (99.999%).

8. The method for improving fatigue strength of deformed Mg-Al magnesium alloy according to claim 1, characterized in that: The step 4 is specifically as follows: a) Homogenization treatment: The peeled high-quality AZ31 alloy ingot is homogenized in a protective atmosphere at a homogenization temperature of 400-420°C for 20-30 hours, and the cooling method is water quenching; b) Plastic forming: The high quality AZ31 alloy ingot homogenized ingot is thermomechanically treated by plastic forming methods such as extrusion, forging and rolling.

9. A method for improving fatigue strength of deformed Mg-Al magnesium alloy according to claim 8, characterized in that: For extrusion forming, the preheating temperature of the billet is 420℃±20℃, the extrusion die temperature is 420℃±20℃, and the temperature is kept for 8h; the extrusion feed speed is 0.6mm / s, the extrusion barrel temperature is set at 420℃±20℃, and the extrusion ratio is set at 57.6; And the preheating temperature of the billet, the temperature of the extrusion die and the temperature of the extrusion barrel are the same; At this point, the preparation of fatigue-resistant AZ31 deformed alloy, namely fatigue-resistant Mg-Al magnesium alloy, is completed.